Product Differentiation on Roads: Second-Best Congestion Pricing with Heterogeneity under Public and Private Ownership - Erik T. Verhoef; Kenneth A. Small (Tinbergen Institute, 1999)
We explore the properties of various types of public and private pricing on acongested road network with heterogeneous users and allowing for elasticdemand. Heterogeneity is represented by a continuum of values of time. Thenetwork consists of both serial and parallel links, which allows us to modelsecond-best pricing restrictions on either complementary or substitute links,while still accounting for interaction between different groups on sharedlinks (e.g. in city centres). We find that private (revenue-maximizing)pricing is much less efficient than public pricing, whether on the partial orthe full network; but this difference is mitigated by the productdifferentiation made possible by heterogeneous users. Ignoring heterogeneitycauses the welfare benefits of second-best pricing of one parallel link, apolicy currently receiving favourable consideration, to be dramaticallyunderestimated. Product differentiation produces some unexpecteddistributional effects, including the possibility that first-best pricing canresult in one of the parallel routes being both more congested than withoutpricing.
Keywords: R41; R48; D62; 330; congestion; road pricing; networks; second-best; Straßenbenutzungsgebühr; Bottleneck; Theorie